Who is afraid of capital mobility? On labor taxation and the level of public services in an open economy - Jens Oliver Lorz; Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper deals with the impact of international capital mobility on labor taxes and the size of the public sector. It employs a model of the labor market, where national trade unions arc able to set wages above the competitive level. In a closed economy, a higher labor tax raises wage demands of the unions and thus increases the distortion on the labor market. With perfect international capital mobility, competition between trade unions leads to full employment, irrespective of the labor tax rale. The distorting effect of the labor tax vanishes and governments arc able to increase the supplied quantity of public services to the first best level.
Keywords: F20; J38; J51; 330; Capital Mobility; Labor Taxation; Kapitalmobilität; Lohnsteuer; Öffentlicher Sektor; Lohnverhandlungen; Standortwettbewerb; Theorie